The Dynamic Role of PD-1, Vitamin D, RANKL, and Sclerostin in Iraqi Patients with Systemic Lupus Erythematosus - Ismael, Anwar Khalil; Alabassi, Hazima Mossa (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
Systemic lupus erythematosus (SLE) is a chronic, autoimmune disease, with a wide range of clinical symptoms. Some studies have indicated the association between RANKL, Sclerostin, PD-1, and vitamin D concentrations and the pathogenesis of SLE. The current study aimed to evaluate the role of RANKL, Sclerostin, PD-1 and vitamin D in the pathogenesis of SLE. The study included 180 females diagnosed SLE patients and healthy control (60 females as early diagnosed patients without treatment, 60 females as patients under treatment with (prednisolone, and hydroxychloroquine), and 60 females healthy as a control group, with ages ranging from 20 to 45 years. The serum concentration levels of RANKL, Sclerostin, PD-1 and vitamin D were assessed by Enzyme linked immunosorbent assay (ELISA). The results of the current study showed no significant differences in the serum levels of RANKL and Sclerostin in both SLE patients’ groups (early diagnosed group and treated) compared with the control group (p<0.05). The serum level of PD-1 was significantly higher in both SLE patients’ groups compared with the control group (p<0.05). The serum level of vitamin D was significantly lower in both SLE patient groups compared with the control group (p<0.05). Based on these results, PD-1 may be considered a good therapeutic target for SLE and the level of vitamin D must be sufficient level especially in SLE patients.